Effect of friction on levelling of the maxillary canine with NiTi superelastic wire - an in silico experiment using a finite element method - Rikou Miyawaki; Yukiko Yokoi (Clinical and Investigative Orthodontics)
Purpose To clarify the effect of friction on the levelling process using a NiTi superelastic wire, the levelling process was simulated using a finite element method.Materials and methods The maxillary right canine, which was intruded by 2 mm, was levelled using a 0.014 inch or 0.016 inch NiTi round wire. The wire was supported by two fixed brackets with 0.018 × 0.025 inch slots. The canine, alveolar bone, and bracket were rigid bodies, while the periodontal ligament (PDL) was a nonlinear elastic material. Kinetic friction was caused by contact forces acting on the wire and the bracket slot. Additionally, when the wire was securely ligated to the bracket slot, a constant frictional force caused by the ligation was directly applied to the wire. As the levelling force was applied to the canine, it moved by accumulating the initial tooth movement caused by elastic deformation of the PDL.Results In the case without friction caused by ligation, although the kinetic friction decreased the levelling force during the early levelling stage, the progress of levelling remained unchanged. In the case with friction caused by ligation, as the ligation friction increased, the levelling force decreased, reducing the levelling speed. Furthermore, the levelling process was impeded when the friction caused by ligation reached a critical value.Conclusion When using passive self-ligating brackets, the friction is caused only by levelling forces, which have almost no effect. When the wire is ligated securely to the bracket, additional friction is generated, hindering the levelling process.